2004
DOI: 10.1186/ar1156
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 60 COX = cyclooxygenase; CRH = corticotropin-releasing hormone; FGF = fibroblast growth factor; HEV = high endothelial venules; HGF = hepatocyte growth factor; ICAM = intercellular adhesion molecule; IL = interleukin; IFN = interferon; MCP-1 = monocyte chemoattractant protein-1; MHC = major histocompatibility complex; MMP = matrix metalloproteinase; OA = osteoarthritic; RA = rheumatoid arthritis; TIMP = tissue inhibitor of metalloproteinase; TNF = tumour necrosis factor; VCAM = vascular cell adhesion molecule;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 124 publications
1
20
0
Order By: Relevance
“…Failure to form functional mature vessels is known to contribute to oedema formation, swelling and inflammation in RA joints (reviewed in [55]). Interestingly, recent work in angptl-4 -deficient mice has shown that ANGPTL-4 is important in vessel maturation because mice lacking ANGPTL-4 exhibited disruption of endothelial adherens junctions and pericyte coverage, with impaired angiogenesis and vascular leakage as a result [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to form functional mature vessels is known to contribute to oedema formation, swelling and inflammation in RA joints (reviewed in [55]). Interestingly, recent work in angptl-4 -deficient mice has shown that ANGPTL-4 is important in vessel maturation because mice lacking ANGPTL-4 exhibited disruption of endothelial adherens junctions and pericyte coverage, with impaired angiogenesis and vascular leakage as a result [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…(4) Third possibility is that the inflammatory synovia in RA is with increased proliferation and potent apoptosis of the vascular endothelial cells [25]. The cultivated endothelial cells liberate more ADMA than SDMA [26].…”
Section: Defining the Problemmentioning
confidence: 99%
“…Moreover, other posttranslational modifications of LDL may also account for NO uncoupling [ 34 ]. In the rheumatoid synovia, endothelial cells undergo a phenotypic change characterized by an increase in activation, angiogenesis, and apoptosis [ 35 ]. The increased turnover of endothelial cells as well as the increased number of proliferating cells associated with angiogenetic microenvironment of the inflamed joint may be a source of methylarginines.…”
Section: Physiopathology Of Adma and Endothelial Dysfunction In Rhmentioning
confidence: 99%